2003
DOI: 10.2308/aud.2003.22.2.17
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Audit Committee Characteristics and Audit Fees

Abstract: This study examines the association between audit committee characteristics and audit fees, using data gathered under the recent SEC fee disclosure rules. We hypothesize that audit fees will be positively associated with audit committee independence, financial expertise, and meeting frequency. We examine a sample of 492 nonregulated, Big 5-audited firms that filed proxy statements with the SEC in the period from February 5, 2001 to June 30, 2001. We find that audit committee independence (defined as an audit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

65
562
14
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 559 publications
(654 citation statements)
references
References 20 publications
65
562
14
13
Order By: Relevance
“…However, this finding contrasted that of [11,14,17]. The results found in [12] on the relationship between audit committee expertise and audit fees also contrasted with the findings of [13,16,15,17]. Similarly, [15] and [17] found that the frequency of audit committee meetings has a significant and positive relationship with audit fees did not support the findings of [11] and [12].…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations
“…However, this finding contrasted that of [11,14,17]. The results found in [12] on the relationship between audit committee expertise and audit fees also contrasted with the findings of [13,16,15,17]. Similarly, [15] and [17] found that the frequency of audit committee meetings has a significant and positive relationship with audit fees did not support the findings of [11] and [12].…”
Section: Introductioncontrasting
confidence: 54%
“…[15] and [12] found that audit committee independence has a significant and positive relationship with audit fees. However, this finding contrasted that of [11,14,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hsu & Petchsakulwong, 2010;Khanchel, 2007;Kyereboah-Coleman, 2007;Mohd et al, 2009). Abbott, Peters and Raghunandan (2003) stated that frequent meetings of audit committee may lead to the improvement of the financial accounting processes which in turn, leads to superior performance. Sharing the same perspective is the resource dependence theory that stated that the board meeting helps the board to valuate and pursue a board business from time to time and to solve any problem encountered by employees (Pearce & Zahra, 1992;Pfeffer, 1987).…”
Section: Audit Committee Meeting and Firm Performancementioning
confidence: 99%